Improvement Of Polyhydroxyalkanoate Synthase From Wautersia Eutropha By In Vitro Evolution [QH460. N842 2005 f rb]. - Mohd Yahaya, Normi (2005)
Polyhydroxyalkanoates (PHA) are polyesters synthesized by various bacteria as intracelullar carbon and energy storage material under excess carbon and limiting nutrient conditions. In the recent decades, PHAs have attracted considerable attention due to similarity in their physical properties to petrochemical-based polyesters.